Derivation of a Reliable and Consistent Volume Delay Functions for Town Road Network Based on Users Feedback - A., Zulkiple; Sharifah, Awang (Penerbit UMP, 2012)
Volume delay function (VDF) of a road network is one of the key elements when running trip assignment in traffic modeling exercises. Often the modeler opts to adjust the tedious road network and trip matrices models while keeping the VDF constant although the later was merely adopted from prevailing database without making effort to review its validity. Adjusting the VDF is time consuming and a modeler really has to be familiar with the study area road network and experience driving on every road during peak and off peak hours. Furthermore the results are still subjected to variations due to time and day difference even for a team of well- trained numerators. As such there seem to be an opportunity to get simultaneous responds say during AM peak hours from a comprehensive users’ feedback survey. This paper presents the methodology on deriving VDF for a town road network based on users’ feedback and compare the validity of the study approach with various VDF models such as Spiess’s conical volume function, Singapore model, the Indonesian Highway Capacity Manual (MKJI) volume delay function and the well-known US Bureau of Public Road (BPR) function.